The effect of transient receptor vanilloid 4 (TRPV4) ligands on fatty acid-binding protein 4 (FABP4) adipocytes signalling in different duration of differentiation - Mohd Radzuan, Hazulin; Bennett, Andrew J.; Cole, Mark (2021)
Introduction: Fatty acid-binding protein 4 (FABP4) is one of the adipocyte lipid chaperone proteins (LCPs) and is commonly related to metabolic diseases. The progression of obesity and diabetes was thought to be associated with increased mitochondrial calcium uptake. Ligands of transient receptor potential vanilloid 4 (TRPV4) are known to affect adipocytes’ intracellular calcium concentration. This study was intended to determine the effect of TRPV4 ligands on adipocytes FABP4 signalling at different phases of cell differentiation. Methods: Primary adipocyte cultures from male Wistar rats were differentiated in high glucose media (17.5 mM/L) and divided into 2 groups. The first group was differentiated up to day5, while the other group was up to day9. They were treated with 100nM GSK101 (TRPV4 agonist) and 500nM HC067 (TRPV4 antagonist) for 24-hours. RNA extracted from adherent adipocytes was subjected for RT-PCR analysis, while cell lysate and conditioned media were collected for western blotting. The data was interpreted by GraphPad Prism Software (San Diego) and ImageJ (National Institutes of Health, USA). Results: GSK101 markedly upregulated FABP4 expression, whereas HC067 caused its downregulation among day9 treated groups (p<0.05). A significant reduction of cytosolic FABP4 was observed in the day5-HC067 treated group (p<0.001), unlike those treated on day9. Despite TRPV4 ligands stimulation, FABP4 secretion was only observed on day9 differentiation. Conclusion: Since FABP4 was only secreted by mature adipocytes and increased intracellular calcium affects its signalling time-dependently, these help us to understand the association of adipocytes LCPs regulation towards progression of metabolic diseases.